The Push–Pull Factors of Physician–System Integration: A Qualitative Study of Washington State Healthcare Executives - Nguyen, Ann M. (J Healthc Manag, 2019)
The transition from volume- to value-based care calls for closer working relationships between physician groups and health systems. Healthcare executives are in the position of determining when and how physician groups are integrated into healthcare systems. Leveraging the theory of migration, we aim to describe where physician–system integration is headed and offer recommendations on how executives can respond to physician migration to and from integration. We conducted 25 semistructured interviews with CEOs, chief medical officers, chief financial officers, and physician group chief executives from eight of Washington State’s largest integrated delivery systems. These executives predicted tighter integration and more forced alignment; however, some clinician executives were skeptical about whether the physician employment model will be the right course despite the growing demand from younger physicians. The results of these interviews suggest that integration will be driven by push and pull factors stemming from five prevailing forces: social (community), social (physicians), economic, political, and technological. Understanding the factors that influence physicians’ decisions to migrate can provide insight for and guidance to executives contemplating integration in the current climate.